Peningkatan Keterampilan Berbicara Siswa pada Mata Pelajaran IPAS Melalui Model Kooperatif Tipe Jigsaw di Kelas V SD : Penelitian - Adinda Ajeng Rindu Astuti; Alif Mudiono; Mochammad Amirudin Ichda (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
By having students work in groups, the Jigsaw learning method hopes to boost their comprehension of the subject. The purpose of this research is to examine the effectiveness of the Jigsaw learning method in enhancing students' participation in group projects at Blimbing 02 Elementary School Malang, specifically in class V. The purpose of this qualitative study is to apply the Jigsaw method of group learning to enhance students' public speaking abilities via the use of the Classroom Action Research (CAR) approach. The study took place in April and May of 2025 at Blimbing 02 Elementary School in Malang. Students in the fifth grade at Blimbing 02 Elementary School in Malang served as the subjects of the study, and information was gathered through documentation, interviews, and observation. Based on the study's findings, student participation was low in the first cycle (44% of students actively speaking), but it increased significantly to 76% in the second cycle. Students' speaking abilities have improved with the help of the Jigsaw method, but to get the best results, it needs to be fine-tuned for each individual.